Structural, redox and isotopic behaviors of iron in geological silicate glasses: A NRIXS study of Lamb-Mössbauer factors and force constants. (15th March 2022) - Roskosz, Mathieu; Dauphas, Nicolas; Hu, Justin; Hu, Michael Y.; Neuville, Daniel R.; Brown, Dennis; Bi, Wenli; Nie, Nicole X.; Zhao, Jiyong; Alp, Esen E.
Abstract: We report a combined conventional Mössbauer and synchrotron Nuclear Resonant Inelastic X-ray Scattering (NRIXS) study of a series of basalt, andesite, dacite, and rhyolite glasses at temperatures ranging from 5 to 1223 K. These glasses were synthesized under controlled oxygen fugacities and span a wide range of Fe 3+ /Fetot ratios. As expected from theory, we find that in these glasses, the inverse of the Lamb-Mössbauer factor (the recoil-free fraction) correlates linearly with the fraction of the conventional Mössbauer spectrum that can be ascribed to Fe 3+ . Extrapolating the linear relationships to pure Fe 3+ and Fe 2+ endmembers yields a ratio for the Lamb-Mössbauer factors C of Fe 3+ and Fe 2+ of 1.203 ± 0.017 (1σ), with no clear dependence on the chemical composition of the glass. We show that the materials studied follow the harmonic approximation up to 1223 K for olivine and 773 K for basaltic glass, allowing us to extrapolate C in temperature. The temperature-dependence of C is well approximated by the formula C = 1.203 ± 0.033 T / 300 over the temperature range 50–750 K. This calibration is used to correct previous redox ratio determinations. We investigate how chemical composition and iron redox state influence the mean force constant of iron in glasses, a key driver of Fe isotopic fractionation during magma generation and differentiation. As previously documented by Dauphas et al. (2014), we find clear correlation between bond strength and iron redox ratio that is secondarily modulated by coordination effects in more alkali-rich felsic magmas. New data on simplified glass compositions reveal that network modifiers, notably K and Na, seem to exert an important control on Fe 2+ bond strengths. The refined ratio of Mössbauer factors for Fe 2+ and Fe 3+ is used to improve on calibrations of iron redox state in geological glasses using XANES spectroscopy. We reevaluate the Fe 3+ /Fetot ratio of MORBs based on previously published XANES and Mössbauer data. 0.087 ± 0.005